2014
DOI: 10.1021/jm501230c
|View full text |Cite
|
Sign up to set email alerts
|

Astemizole Arrests the Proliferation of Cancer Cells by Disrupting the EZH2-EED Interaction of Polycomb Repressive Complex 2

Abstract: Polycomb Repressive Complex 2 (PRC2) modulates the chromatin structure and transcriptional repression by trimethylation lysine 27 of histone H3 (H3K27me3), a process that necessitates the protein-protein interaction (PPI) between the catalytic subunit EZH2 and EED. Deregulated PRC2 is intimately involved in tumorigenesis and progression, making it an invaluable target for epigenetic cancer therapy. However, until now, there have been no reported small molecule compounds targeting the EZH2-EED interactions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 75 publications
(122 reference statements)
3
73
0
Order By: Relevance
“…Strikingly, in contrast to the anticipated enhancement of viral gene expression, each compound suppressed viral IE gene transcription in a dose-dependent manner. Similarly, treatment with astemizole, a compound that interferes with the association of EZH2/1 with the chromatin binding subunit of the PRC2 complex (EED, embryonic ectoderm development) (24), also suppressed viral IE gene expression ( Fig. 1A and E to F).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Strikingly, in contrast to the anticipated enhancement of viral gene expression, each compound suppressed viral IE gene transcription in a dose-dependent manner. Similarly, treatment with astemizole, a compound that interferes with the association of EZH2/1 with the chromatin binding subunit of the PRC2 complex (EED, embryonic ectoderm development) (24), also suppressed viral IE gene expression ( Fig. 1A and E to F).…”
mentioning
confidence: 87%
“…More recently, inhibitors of the histone H3K27 methyltransferases EZH2 and EZH1 (EZH2/1) have been developed as potential therapeutics for treating cancers with EZH2 gain-of-function mutations (22)(23)(24)(25)(26)(27)(28)(29)(30). As components of Polycomb repressive complex 2 (PRC2), EZH2/1 mediate gene repression primarily through propagation of H3K27me3, which results in domains of nucleosomal compaction (31)(32)(33).…”
mentioning
confidence: 99%
“…Stabilized alpha-helix of EZH2 (SAH-EZH2) peptides disrupt the EZH2/EED interaction and decrease the EZH2 levels leading to decreased methyltransferase activity leading to growth arrest and differentiation of MLL-AF9 leukemic cells [109]. Similarly, Astemizole is a small molecule inhibitor of EZH2/EED interaction which destabilizes PRC2 complex decreasing the proliferation of lymphoma cells [110]. Finally, CPI-1205 selectively inhibits the interaction of EZH2 with PRC2 complex and is currently evaluated in a phase 1 clinical trial in patients with B-cell lymphomas (NCT02395601).…”
Section: Targeting Of Ezh2 For Cancer Therapymentioning
confidence: 99%
“…Recently, it has been identified that Astemizole, a drug previously used in the treatment of seasonal allergic rhinitis, is an inhibitor of the EED/EZH2 protein-protein interaction. Astemizole competes with EZH2 for the binding with EED, destabilizing PRC2 complex and inducing cell cycle arrest in leukemia cells [112] . Interestingly, the combination treatment of SAH-EZH2 or astemizole and various SAM analogues produced a significant synergistic effect on lymphoma cells [111,112] , indicating that the suppression of catalytic activity and the disruption of PRC2 complex could influence different pathways and a combinatorial drug therapy can be a more effective therapeutic strategy.…”
Section: Inhibition Of the Interaction Between Ezh2 With Other Prc2 Smentioning
confidence: 99%